Education of women riverside in the municipality of Breves - Cleide Carvalho de Matos; Manuelle Espíndola dos Reis (Revista Brasileira de Educação do Campo, 2018)
This work aims to understand the gender approach that permeates the curricular proposal of the elementary schools of the countryside of the municipality of Breves, to identify what is affirmed about the riverside woman in the mentioned curricular proposal and evaluates what knowledge about the riverside woman is included in the document. The study was realized through bibliographical and documentary research. The document analyzed was the curricular proposal of the schools of the countryside of the municipality of Breves, elaborated in 2012 and revised in 2014. The main theorists who foundation this work were Scott (2005), Louro (2007, 2005), Meyer (2007), Oliveira 2004), (Pinto, 2001). The curricular proposal of the countryside schools presents a fragile discussion about gender, based on a biological conception, in which we do not perceive the presence of the different identities, which, although silenced, are present in the school. In the document we did not identify any reference to the riverside woman, her stories of struggle and resistance were left aside from the discussions of a document that legitimizes what should be taught and learned in the countryside schools.